DEVELOPMENT OF PINK DISEASE ON VARIOUS AGES OF Acacia crassicarpa CUNN EX. BENTH. - Suryantini, Rosa; Soelistijono, Soelistijono (Universitas Lampung, 2020)
Development of pink disease on the various ages of Acacia crassicarpa Cunn Ex. Benth.. The increase in the value of pulpand paper exports in Indonesia is partly due to the development of industrial forest plantations of acacia on peatlands. Acaciacrassicarpa grows well on peatlands with high productivity. However, the development of pink disease is a threat to thegrowth of A. crassicarpa, both in the nursery and in the field. This study aimed at examining the development of pink diseaseon the various ages of A. crassicarpa. The study was conducted using census method on plants at aged 4, 24 and 42 months.Variables observed were symptoms, incidence, and severity of disease. Data were analyzed descriptively and regressively tounderstand the relationship between the incidence and severity of the disease and the age of the plant. The results showedthat the symptoms that appearing at the seedling level were similar to those the sapling, poles and tree level. The presence ofthin colonies of cobweb-like (cobweb stage), mycelia aggregation from the cobweb stage (pseudonodular stage), and theappearance of pustules and pink incrustation (teleomorph stage) were common symptom. However, disease incidence andseverity were moderate at the seedling and mild at the saplings, poles and trees level. The incidence and severity of diseasedecreased with increasing age.